Faktor-faktor yang mempengaruhi impor beras di Indonesia Tahun 2001-2019 - Mashithoh Azzahra, Dian; Amir, Amri; Hodijah, Siti (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The objectives of this study are as follows: (1) To determine and analyze the development of rice imports, rice production, population, and rice consumption in Indonesia in 2001-2019. (2) To determine and analyze the effect of rice production, population, and rice consumption on rice imports in Indonesia in 2001-2019. Based on the research results, (1) Rice imports in Indonesia fluctuate every year, and the development of the population in Indonesia has increased. The effect of rice consumption in Indonesia fluctuates from year to year. The story of rice production in Indonesia also fluctuates. (2) The regression results show that the population has a positive and significant effect on rice imports in Indonesia. Rice consumption has a positive and significant effect on rice imports in Indonesia. Rice production does not affect rice imports in Indonesia. Â Keywords: Population, Rice consumption, Rice production